THE INFLUENCE OF THE LABKESDA INFORMATION SYSTEM (SIL) AND EMPLOYEE WORK MOTIVATION ON EMPLOYEE SERVICE PERFORMANCE AT UPTD HEALTH LABORATORY THE SUKABUMI CITY - Susanti Susanti; Ike Rachmawati; Munandi Saleh (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This research is a type of quantitative research which aims to find out whether there is an influence of the regional health laboratory information system (SIL) and employee work motivation on employee performance. The research population was employees of the Sukabumi City Health Laboratory UPTD and community health center network laboratories with a population of 40 people using a saturated or census sample. For the purposes of data collection, the author used two methods, namely primary data and secondary data. Primary data consists of questionnaires, interviews and participant observation. Secondary data collection takes the form of library research which includes books, scientific writings, journals, documents and previous studies related to the research problem. Data analysis consists of validity testing, reliability testing, and hypothesis testing. The validity test uses the Pearson product moment correlation formula which is processed using SPSS version 26. To see whether the resulting regression model is the most appropriate model and has the smallest error, analytical testing is used using the R2 test (coefficient of multiple determination), the F test, and the Q test. The results of the research show that the Regional Health Lab Information System (SIL) has an influence on employee performance, with increasing SIL contributing to increasing employee work efficiency and effectiveness. Work motivation also has a significant impact on employee performance, where higher levels of motivation undermine better performance. Furthermore, research shows that these two factors, SIL and work motivation, interact positively and complement each other in improving employee performance. The implication of these findings is the importance of management attention to good implementation of SIL and the creation of a motivating work environment to improve overall employee performance.